Performances of HTLV serological tests in diagnosing HTLV infection in high-risk population of São Paulo, Brazil Desempenho de testes sorológicos para o diagnóstico de infecção por HTLV em população de alto-risco de São Paulo, Brasil - Fabrício Jacob; Elizabeth de los Santos-Fortuna; Raymundo Soares Azevedo; Adele Caterino-de-Araujo (Revista do Instituto de Medicina Tropical de São Paulo, 2007)
Testing problems in diagnosing human T-lymphotropic virus (HTLV) infection, mostly HTLV-II, have been documented in HIV/AIDS patients. Since December 1998, the Immunology Department of Instituto Adolfo Lutz (IAL) offers HTLV-I/II serology to Public Health Units that attend HTLV high-risk individuals. Two thousand, three hundred and twelve serum samples: 1,393 from AIDS Reference Centers (Group I), and 919 from HTLV out-patient clinics (Group II) were sent to IAL for HTLV-I/II antibodies detection. The majority of them were screened by two enzyme immunoassays (EIAs), and confirmed by Western Blot (WB 2.4, Genelabs). Seven different EIA kits were employed during the period, and according to WB results, the best performance was obtained by EIAs that contain HTLV-I and HTLV-II viral lysates and rgp21 as antigens. Neither 1st and 2nd, nor 3rd generation EIA kits were 100% sensitive in detecting truly HTLV-I/II reactive samples. HTLV-I and HTLV-II prevalence rates of 3.3% and 2.5% were detected in Group I, and of 9.6% and 3.6% in Group II, respectively. High percentages of HTLV-seroindeterminate WB sera were detected in both Groups. The algorithm testing to be employed in HTLV high-risk population from São Paulo, Brazil, needs the use of two EIA kits of different formats and compounds as screening, and because of high seroindeterminate WB, may be another confirmatory assay. Problemas nos testes diagnósticos de infecção pelos vírus linfotrópicos de células T humanas (HTLV), principalmente HTLV-II, têm sido observados em pacientes com HIV/Aids. Desde Dezembro de 1998, a Seção de Imunologia do Instituto Adolfo Lutz (IAL) oferece a sorologia para HTLV-I/II para Serviços de Saúde Pública que atendem populações consideradas de risco para esta infecção. Duas mil trezentas e doze amostras de soro: 1.393 de Centros de Referência em Aids (Grupo I) e 919 de Clínicas de Especialidade em HTLV (Grupo II) foram encaminhadas para o IAL para a pesquisa de anticorpos anti-HTLV-I/II. A maioria delas foram testadas por dois ensaios ...